Stochastic 16-State Model of Voltage Gating of Gap-Junction Channels Enclosing Fast and Slow Gates - Paulauskas, Nerijus (The Biophysical Society, 2012)
Gap-junction (GJ) channels formed of connexin (Cx) proteins provide a direct pathway for electrical and metabolic cell-cell interaction. Each hemichannel in the GJ channel contains fast and slow gates that are sensitive to transjunctional voltage (V(j)). We developed a stochastic 16-state model (S16SM) that details the operation of two fast and two slow gates in series to describe the gating properties of homotypic and heterotypic GJ channels. The operation of each gate depends on the fraction of V(j) that falls across the gate (V(G)), which varies depending on the states of three other gates in series, as well as on parameters of the fast and slow gates characterizing 1), the steepness of each gate's open probability on V(G); 2), the voltage at which the open probability of each gate equals 0.5; 3), the gating polarity; and 4), the unitary conductances of the gates and their rectification depending on V(G). S16SM allows for the simulation of junctional current dynamics and the dependence of steady-state junctional conductance (g(j,ss)) on V(j). We combined global coordinate optimization algorithms with S16SM to evaluate the gating parameters of fast and slow gates from experimentally measured g(j,ss)-V(j) dependencies in cells expressing different Cx isoforms and forming homotypic and/or heterotypic GJ channels.